STRATEGI PENGEMBANGAN KESATUAN PENGELOLAAN HUTAN (KPH) MENUJU KEMANDIRIAN UPT (UNIT PELAKSANA TEKNIS) (Studi Kasus UPT-KPH Jeneberang II Meliputi Kabupaten Bantaeng, Bulukumba, dan Sinjai) - Andi Sri Ekawati Syam; Nuraeni Nuraeni; Iskandar Hasan (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2023)
This study aims to (1) analyze internal and external environmental factors that determine the independence of forest management by UPT-KPH Jeneberang II, (2) formulate a strategy for developing UPT-KPH Jeneberang II towards independence. Data was collected using field survey methods, in-depth interviews and literature studies. Data were analyzed descriptively and SWOT. The results showed that the internal, and external environmental factors that determine the independence of UPT-KPH Jeneberang II in forest management are Human Resources (HR) according to the required competencies and forest management planning documents (strengths) and forest restoration (weaknesses). Meanwhile, external environmental factors are determined by FMU business management rules (opportunities) and the forest area boundary demarcation has not been implemented (threats). Based on these supporting and inhibiting factors, the strategies needed in the development of UPT-KPH Jeneberang II towards independence are (1) Strengthening the implementation of regulations that support KPH business management by KPH HR with the availability of good forest management planning documents, (2) Increasing involvement the parties in the activities of sustainable forest use, management of social aspects, and forest protection and conservation, (3) Utilizing regional regulations to support forest utilization cooperation by encouraging the development of superior and non-superior product commodities